A note on the Sandor-Smarandache function (Journal of Bangladesh Academy of Sciences, 2022)
The Sandor-Smarandache function, denoted by SS(n), is a recently posed Smarandache-type arithmetic function. This paper concentrates on the function SS(210m), where m ( ≥1) is an integer. At the end of the paper, a table giving values of SS(210m) for m = 1(1)100, calculated on a computer, is appended.J. Bangladesh Acad. Sci. 45(2); 255-258: December 2021